A systematic review of the relationship between internet use, self-harm and suicidal behaviour in young people: The good, the bad and the unknown. - Amanda Marchant; Keith Hawton; Ann Stewart; Paul Montgomery; Vinod Singaravelu; Keith Lloyd; Nicola Purdy; Kate Daine; Ann John (PLoS ONE)
Background Research exploring internet use and self-harm is rapidly expanding amidst concerns regarding influences of on-line activities on self-harm and suicide, especially in young people. We aimed to systematically review evidence regarding the potential influence of the internet on self-harm/suicidal behaviour in young people. Methods We conducted a systematic review based on an electronic search for articles published between 01/01/2011 and 26/01/2015 across databases including Medline, Cochrane and PsychInfo. Articles were included if: the study examined internet use by individuals who engaged in self-harm/ suicidal behaviour, or internet use clearly related to self-harm content; reported primary empirical data; participants were aged under 25 years. New studies were combined with those identified in a previous review and subject to data extraction, quality rating and narrative synthesis. Results Forty-six independent studies (51 articles) of varying quality were included. Perceived influences were: positive for 11 studies (38191 participants); negative for 18 studies (119524 participants); and mixed for 17 studies (35235 participants). In contrast to previous reviews on this topic studies focused on a wide range of internet mediums: general internet use; internet addiction; online intervention/treatment; social media; dedicated self-harm websites; forums; video/image sharing and blogs. A relationship between internet use and self-harm/suicidal behaviour was particularly associated with internet addiction, high levels of internet use, and websites with self-harm or suicide content. While there are negative aspects of internet use the potential for isolation reduction, outreach and as a source of help and therapy were also identified. Conclusions There is significant potential for harm from online behaviour (normalisation, triggering, competition, contagion) but also the potential to exploit its benefits (crisis support, reduction of social isolation, delivery of therapy, outreach). Young people appear to be increasingly using social media to communicate distress, particularly to peers. The focus should now be on how specific mediums' (social media, video/image sharing) might be used in therapy and recovery. Clinicians working with young people who self-harm or have mental health issues should engage in discussion about internet use. This should be a standard item during assessment. A protocol for this review was registered with the PROSPERO systematic review protocol registry: (http://www.crd.york.ac.uk/prospero/display_record.asp?ID=CRD42015019518).